Preparation method of high-dielectric-constant fiber-reinforced solid electrolyte

The nanofiber framework of strontium barium titanate was prepared by electrospinning, and a high-dielectric constant fiber reinforced solid electrolyte was constructed, which solved the safety hazards of liquid electrolytes in traditional lithium batteries and the limitations of improving the conductivity of composite solid electrolytes, and achieved high-performance solid electrolytes, meeting the requirements of high energy density and safety.

CN119833744AActive Publication Date: 2025-04-15HARBIN UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510041586.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The liquid electrolytes of traditional lithium batteries have safety hazards such as liquid leakage and flammability, and may lead to the formation of lithium dendrites at high voltages, which in turn can cause battery explosions and other problems. At the same time, the existing composite solid electrolytes have limitations in improving conductivity, and the polymer matrix is ​​prone to isolate inorganic fillers, hindering the formation of continuous ion channels.

Method used

The nanofiber framework of barium strontium titanate (BST) was prepared by electrospinning and used to construct a high dielectric constant fiber-reinforced solid electrolyte. This method significantly increases the contact area between BST and poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP)/lithium bisfluorosulfonimide (LiFSI) electrolyte, avoiding particle aggregation, thereby improving the electrochemical performance of the electrolyte.

Benefits of technology

An ion conductivity up to 6.3×10-4S/cm and a lithium ion migration number of 0.45 were achieved, with an electrochemical window of 4.56V, and the capacity retention rate exceeded 87% in the cycle test, showing excellent cyclic stability and long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833744A_ABST
    Figure CN119833744A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a solid electrolyte, in particular to a preparation method of a high-dielectric-constant fiber-reinforced solid electrolyte. The method comprises the following steps: 1, preparing barium strontium titanate nanofibers; and 2, preparing the fiber-reinforced solid electrolyte. The barium strontium titanate nanofiber skeleton is prepared by an electrostatic spinning method and is used for constructing the quasi-solid electrolyte; the barium strontium titanate nanofiber skeleton has a self-supporting stable structure and a high specific surface area, the contact area between the BST and the poly (vinylidene fluoride-co-hexafluoropropylene) / lithium bis (fluorosulfonyl) imide electrolyte is remarkably increased, and the particle aggregation phenomenon is avoided, so that the electrochemical performance of the electrolyte is remarkably improved. Especially, BST as a ferroelectric has special electrical properties, is helpful for improving the interface stability and reducing the interface impedance in a battery, further improves the migration rate of lithium ions in an electrolyte, has excellent electrochemical properties, and can meet the requirements of high energy density and safety in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a solid electrolyte. Background Art

[0002] In order to alleviate the global energy crisis and respond to climate change, the new energy power generation and electric vehicle industries have developed rapidly in recent years, driving the market demand for battery technology. In particular, higher requirements are placed on the energy density and safety of batteries. However, the energy density of traditional lithium-ion batteries is close to the theoretical limit, and new technological breakthroughs are urgently needed. Lithium metal anodes have become an ideal choice for high energy density energy storage due to their high theoretical energy density (3860mAh / g) and low reduction potential (-3.04V vs. standard hydrogen electrode), and have therefore attracted a lot of research attention.

[0003] Traditional lithium batteries use organic liquid electrolytes, which face safety hazards such as leakage and flammability, and may cause the formation of lithium dendrites under high voltage, which in turn may cause battery explosion and other problems. To solve these problems, solid electrolytes (SSE) are considered to be ideal materials to replace liquid electrolytes, which can increase battery energy density and improve safety. The performance of solid electrolytes directly determines the overall performance of solid-state batteries. In particular, how to obtain solid electrolytes with high lithium ion conductivity at room temperature has become the key to current research.

[0004] The electrolytes of solid-state lithium batteries are mainly divided into three categories: inorganic solid electrolytes, organic polymer solid electrolytes and composite solid electrolytes (CSE). Although inorganic solid electrolytes have excellent electrical conductivity, they have the disadvantages of being brittle and having high impedance at the electrode interface; polymer electrolytes have low mechanical strength and low electrical conductivity at room temperature (10 -5 ~10 -4 S / cm). Therefore, it is an effective strategy to develop composite solid electrolytes by combining the high conductivity of inorganic electrolytes and the flexibility of polymer electrolytes. However, traditional zero-dimensional or one-dimensional inorganic fillers have limited effect on improving conductivity, and excessive filler content will lead to aggregation, which will reduce conductivity. In addition, the polymer matrix tends to isolate inorganic fillers, hindering the formation of continuous ion channels, thus limiting the further improvement of the performance of composite electrolytes. Summary of the invention

[0005] The purpose of the present invention is to solve the above technical problems existing in the prior art and to provide a method for preparing a high dielectric constant fiber reinforced solid electrolyte.

[0006] A method for preparing a high dielectric constant fiber-reinforced solid electrolyte is specifically completed by the following steps:

[0007] 1. Preparation of barium strontium titanate nanofibers:

[0008] ①, dissolve polyvinyl pyrrolidone in anhydrous ethanol to obtain solution A;

[0009] ②, dissolving barium acetate and strontium acetate in a mixed solution of glacial acetic acid and deionized water to obtain solution B;

[0010] ③. Under magnetic stirring conditions, mix solution A and solution B evenly, then add tetrabutyl titanate and stir evenly to obtain a precursor solution for electrospinning;

[0011] ④, degassing the precursor solution of electrospinning under vacuum conditions for a period of time, then loading it into a syringe, and fixing it on an electrospinning device for electrospinning. After the electrospinning is completed, the obtained fiber film is placed in the air, heated to 800°C to 1100°C, and calcined for a period of time in an air atmosphere at a temperature of 800°C to 1100°C to obtain a barium strontium titanate nanofiber film;

[0012] 2. Preparation of fiber-reinforced solid electrolytes:

[0013] PVDF-HFP and LiFSI were dissolved in N,N-dimethylformamide and magnetically stirred at room temperature for a period of time to obtain a backfill solution; the backfill solution was dripped onto the surface of the barium strontium titanate nanofiber film, and then placed in an oven to dry for a period of time to obtain a high dielectric constant fiber-reinforced solid electrolyte, which was transferred to a glove box filled with argon for use.

[0014] Principle of the present invention:

[0015] The present invention prepares a barium strontium titanate (BST) nanofiber skeleton by an electrospinning method, and uses it to construct a quasi-solid electrolyte; the barium strontium titanate (BST) nanofiber skeleton has a self-supporting stable structure and a high specific surface area, significantly increases the contact area between BST and poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) / lithium bis(fluorosulfonyl)imide (LiFSI) electrolyte, avoids particle aggregation, and thus significantly improves the electrochemical performance of the electrolyte. In particular, BST has special electrical properties as a ferroelectric, which helps to improve interface stability, reduce interface impedance, and further improve the migration rate of lithium ions in the electrolyte in the battery.

[0016] Advantages of the present invention:

[0017] The electrochemical performance test shows that the high dielectric constant fiber-reinforced solid electrolyte prepared by the present invention has a dielectric constant of up to 6.3×10 -4The ion conductivity is 0.01 S / cm, the lithium ion migration number is 0.45, and the electrochemical window is 4.56 V. The high dielectric constant fiber-reinforced solid electrolyte prepared by the present invention is used to assemble a LiFePO4||CSE||Li full battery. In the assembled LiFePO4||CSE||Li full battery, the initial discharge specific capacity at 1C rate is 136 mAh / g. After 170 cycles, the capacity retention rate is still over 87%, showing excellent cycle stability and long life. This indicates that the high dielectric constant fiber-reinforced solid electrolyte prepared by the present invention has excellent electrochemical properties and can meet future high energy density and safety requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Figures 1 and 2 are scanning electron microscope images and XRD patterns, where (a) and (b) are scanning electron microscope images of barium strontium titanate nanofibers prepared in step 1 of Example 1, and (c) is an XRD pattern of barium strontium titanate nanofibers prepared in step 1 of Example 1;

[0019] Figure 2 Ionic conductivity and lithium ion transference number of the high dielectric constant fiber reinforced solid electrolyte prepared in step 2 of Example 1;

[0020] Figure 3 The electrochemical stability window of the high dielectric constant fiber reinforced solid electrolyte prepared in step 2 of Example 1;

[0021] Figure 4 The limiting current density of a lithium symmetric battery assembled using the high dielectric constant fiber reinforced solid electrolyte prepared in step 2 of Example 1 and the PVH solid electrolyte prepared in Comparative Example 1;

[0022] Figure 5 The life of a lithium symmetric battery assembled using the high dielectric constant fiber reinforced solid electrolyte prepared in step 2 of Example 1 and the PVH solid electrolyte prepared in Control Example 1;

[0023] Figure 6 This is a cycle performance curve of a LiFePO4||CSE||Li full battery assembled using the high dielectric constant fiber reinforced solid electrolyte prepared in step 2 of Example 1 at a 1C rate. DETAILED DESCRIPTION

[0024] Specific implementation method 1: This implementation method is a method for preparing a high dielectric constant fiber reinforced solid electrolyte, which is specifically completed according to the following steps:

[0025] 1. Preparation of barium strontium titanate nanofibers:

[0026] ①, dissolve polyvinyl pyrrolidone in anhydrous ethanol to obtain solution A;

[0027] ②, dissolving barium acetate and strontium acetate in a mixed solution of glacial acetic acid and deionized water to obtain solution B;

[0028] ③. Under magnetic stirring conditions, mix solution A and solution B evenly, then add tetrabutyl titanate and stir evenly to obtain a precursor solution for electrospinning;

[0029] ④, degassing the precursor solution of electrospinning under vacuum conditions for a period of time, then loading it into a syringe, and fixing it on an electrospinning device for electrospinning. After the electrospinning is completed, the obtained fiber film is placed in the air, heated to 800°C to 1100°C, and calcined for a period of time in an air atmosphere at a temperature of 800°C to 1100°C to obtain a barium strontium titanate nanofiber film;

[0030] 2. Preparation of fiber-reinforced solid electrolytes:

[0031] PVDF-HFP and LiFSI were dissolved in N,N-dimethylformamide and magnetically stirred at room temperature for a period of time to obtain a backfill solution; the backfill solution was dripped onto the surface of the barium strontium titanate nanofiber film, and then placed in an oven to dry for a period of time to obtain a high dielectric constant fiber-reinforced solid electrolyte, which was transferred to a glove box filled with argon for use.

[0032] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the mass ratio of polyvinyl pyrrolidone to anhydrous ethanol in step 1① is (0.5 g to 0.7 g): (6.5 mL to 9 mL). The other steps are the same as those in specific embodiment 1.

[0033] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the volume ratio of glacial acetic acid to deionized water in the mixed solution of glacial acetic acid and deionized water described in step 1② is (3-5):(1-1). The other steps are the same as those of specific embodiment 1 or 2.

[0034] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the volume ratio of the mass of barium acetate described in step 1 ② to the mixed solution of glacial acetic acid and deionized water is (2g-3g):(9mL-14mL); the volume ratio of the mass of strontium acetate described in step 1 ② to the mixed solution of glacial acetic acid and deionized water is (0.4g-0.5g):(3.5mL-4.2mL). The other steps are the same as those of specific embodiments 1 to 3.

[0035] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the volume ratio of solution A and solution B described in step 1 ③ is (7-8): (6-7); the volume ratio of tetrabutyl titanate described in step 1 ③ to the total volume ratio of solution A and solution B is (1-2): (4-9). The other steps are the same as specific embodiments 1 to 4.

[0036] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the heating rate in step 1 ④ is 5°C / min to 10°C / min; the calcination time in step 1 ④ is 4h to 6h. The other steps are the same as those in specific embodiments 1 to 5.

[0037] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the process parameters of the electrospinning described in step 1④ are: using a 20-gauge needle, setting the liquid supply rate to 1 mL / h to 2 mL / h, the voltage to 18 kV to 25 kV, and the distance between the needle and the receiving electrode plate to 15 cm to 18 cm. The other steps are the same as those of specific embodiments 1 to 6.

[0038] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the degassing time in step 1 ④ is 5 min to 10 min; the thickness of the barium strontium titanate nanofiber film in step 1 ④ is 120 μm to 150 μm. The other steps are the same as those in specific embodiments 1 to 7.

[0039] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the mass ratio of PVDF-HFP described in step 2 to the volume ratio of N,N-dimethylformamide is (0.3g-0.5g):3mL; the mass ratio of LiFSI described in step 2 to the volume ratio of N,N-dimethylformamide is (0.2g-0.3g):3mL. The other steps are the same as specific embodiments 1 to 8.

[0040] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that the volume ratio of the backfill solution described in step 2 to the surface area of ​​the barium strontium titanate nanofiber film is 300 μL: (2 cm 2 ~3cm 2 ); the time of magnetic stirring at room temperature in step 2 is 10h to 12h; the drying temperature in step 2 is 50°C to 55°C, and the drying time is 24h to 48h. The other steps are the same as those in specific embodiments 1 to 9.

[0041] The following examples are used to verify the beneficial effects of the present invention:

[0042] Embodiment 1: A method for preparing a high dielectric constant fiber-reinforced solid electrolyte is specifically completed by the following steps:

[0043] 1. Preparation of barium strontium titanate nanofibers:

[0044] ① Dissolve 0.6 g of polyvinyl pyrrolidone in 7.5 mL of anhydrous ethanol to obtain solution A;

[0045] ②, dissolve 2.043g of barium acetate and 0.410g of strontium acetate in a mixed solution of 7mL of glacial acetic acid and deionized water to obtain solution B;

[0046] The volume ratio of glacial acetic acid to deionized water in the mixed solution of glacial acetic acid and deionized water described in step 1② is 4:1;

[0047] ③. Under magnetic stirring conditions, mix solution A and solution B evenly, then add tetrabutyl titanate and stir evenly to obtain a precursor solution for electrospinning;

[0048] The volume ratio of solution A and solution B described in step 1③ is 15:14;

[0049] The volume ratio of tetrabutyl titanate described in step 1③ to the total volume of solution A and solution B is 7:30;

[0050] ④, the precursor solution of electrospinning was placed in a vacuum condition for degassing for 5 minutes, then loaded into a syringe, and fixed on an electrospinning device for electrospinning. After the electrospinning was completed, the obtained fiber film was placed in the air, heated to 800°C at a heating rate of 5°C / min, and calcined at 800°C in an air atmosphere for 4 hours to obtain barium strontium titanate nanofiber film (BST nanofiber);

[0051] The process parameters of the electrospinning described in step 1④ are: using a 20-gauge needle, setting the liquid supply rate to 1.5 mL / h, the voltage to 18 kV, and the distance between the needle and the receiving electrode to 15 cm;

[0052] The thickness of the barium strontium titanate nanofiber film described in step 1④ is 120 μm;

[0053] 2. Preparation of fiber-reinforced solid electrolytes:

[0054] 0.3 g PVDF-HFP and 0.2 g LiFSI were dissolved in 3 mL N,N-dimethylformamide and magnetically stirred at 25 °C for 12 h to obtain a backfill solution. 300 μL of the backfill solution was dripped onto a surface area of ​​2 cm 2The surface of the barium strontium titanate nanofiber film was dried in an oven at 55°C for 24 hours to obtain a high dielectric constant fiber-reinforced solid electrolyte (BST-PVH quasi-solid electrolyte), which was transferred to an argon-filled glove box for standby use.

[0055] The microscopic morphology of barium strontium titanate nanofibers (BST nanofibers) prepared in step 1 of Example 1 is as follows: Figure 1 As shown in (a, b), the magnification of the scanning electron microscope images is 2k and 70k respectively. It can be seen that the precursor maintains a fibrous structure after calcination, and its diameter is about 500nm. Figure 1 (c) is the X-ray diffraction (XRD) pattern of BST nanofibers, which shows a sharp crystalline peak, which is completely consistent with the standard crystal card PDF#97-009-0006 of BST, indicating that the synthesized material has a high degree of crystallinity.

[0056] The ionic conductivity of the assembled button cell was tested on an electrochemical workstation to obtain the impedance value, and the corresponding ionic conductivity was calculated by substituting it into the formula. The electrolyte was punched into a small disc with a diameter of 16 mm, stainless steel sheets with a diameter of 16 mm were placed on both sides, and finally assembled with a CR2032 battery shell. Each battery was tested at the same room temperature. The calculation formula for ionic conductivity is as follows:

[0057]

[0058] d is the thickness of the electrolyte membrane, R is the impedance tested by electrochemical impedance spectroscopy, and S is the contact area between the electrolyte and the stainless steel sheet.

[0059] The lithium ion transfer number was measured by chronoamperometry and electrochemical impedance spectroscopy at room temperature using two lithium metal sheets as non-blocking electrodes. + Ion migration number (t Li + ). The potential applied to the cell is 10 mV, ranging from 1 to 10 7 Hz measures the electrochemical impedance spectroscopy (EIS) of lithium symmetric batteries before and after polarization. The t of the electrolyte membrane is calculated according to the formula Li + Value. Among them, I0 and I S are the initial current and steady-state current, ΔV is the polarization potential at 10 mV, R0 and R S are the initial state resistance and the steady state resistance.

[0060]

[0061] Figure 2 The ionic conductivity and lithium ion transference number (tLi + ); The test results show that the ionic conductivity of BST-PVH quasi-solid electrolyte is 6.3×10 -4 S / cm,t Li + =0.45. These data indicate that the high dielectric constant of BST helps to improve the dissociation of lithium salts and thus promote the migration of lithium ions.

[0062] Linear sweep voltammetry (LSV) is used to test the electrochemical stability window of the electrolyte. After the stainless steel sheet, electrolyte and lithium sheet are assembled into a battery in sequence, the battery is tested at a rate of 0.2mV / s within 2-6V until the voltage platform of the electrolyte material changes, thereby determining the high-voltage stable potential of the electrolyte membrane.

[0063] The electrochemical stability window of BST-PVH quasi-solid electrolyte was tested by linear sweep voltammetry. Figure 3 As shown;

[0064] Figure 3 It shows that its oxidation potential is 4.56V, which can meet the working requirements of lithium battery positive electrode materials, proving that the electrolyte still maintains stable electrochemical properties under high voltage.

[0065] The lithium symmetric battery assembled using the high dielectric constant fiber reinforced solid electrolyte prepared in step 2 of Example 1 is specifically completed in the following steps:

[0066] The high dielectric constant fiber reinforced solid electrolyte (CSE) prepared in step 2 of Example 1 is cut into discs with a diameter of 16 mm. Under the protection of an inert atmosphere (such as argon), a lithium metal sheet with a diameter of 10 mm is cut as a symmetrical electrode; the lithium metal sheet, the electrolyte membrane and another lithium metal sheet are assembled in a button battery mold in sequence; stainless steel gaskets and springs are used to ensure uniform pressure, and finally, after assembly, the battery is sealed with a button battery sealing machine.

[0067] Figure 4 The limiting current density of the BST-PVH quasi-solid electrolyte was tested by assembling a lithium symmetric battery. Since BST-PVH has a high ionic conductivity and the addition of ceramic materials improves the mechanical strength of the film, the electrolyte can effectively inhibit the growth of lithium dendrites at high current density. The test results show that its limiting current density is 0.9mA / cm 2 , further demonstrating the good stability of BST-PVH at high current density.

[0068] At the same time, at 0.1 mA / cm 2 The current density and 0.1 mAh / cm 2 The battery life test was carried out at the surface capacity. Figure 5 The results show that the lithium symmetric battery assembled using the high dielectric constant fiber reinforced solid electrolyte (BST-PVH quasi-solid electrolyte) prepared in step 2 of Example 1 has a lower overpotential, and the overpotential does not increase significantly after more than 1200 hours of operation. This shows that a good interface contact is formed between the BST-PVH quasi-solid electrolyte and lithium metal, which effectively inhibits the uneven deposition of lithium ions in the solid electrolyte, thereby improving the stability and service life of the battery.

[0069] Figure 4 and Figure 5 PVH is a lithium symmetrical battery assembled using the PVH solid electrolyte prepared in Control Example 1, and BST-PVH is a lithium symmetrical battery assembled using the high dielectric constant fiber reinforced solid electrolyte (BST-PVH quasi-solid electrolyte) prepared in Example 1.

[0070] The LiFePO4||CSE||Li full battery is assembled using the high dielectric constant fiber reinforced solid electrolyte (CSE) prepared in step 2 of Example 1, which is specifically completed in the following steps:

[0071] The high dielectric constant fiber reinforced solid electrolyte (CSE) prepared in step 2 of Example 1 is cut into discs with a diameter of 16 mm, and a LiFePO4 positive electrode sheet with a diameter of 12 mm and a lithium metal negative electrode sheet with a diameter of 14 mm are cut; under the protection of an inert atmosphere (such as argon), the LiFePO4 positive electrode sheet is placed at the bottom of a button battery mold, and the electrolyte membrane and the lithium metal negative electrode sheet are stacked in sequence; then a stainless steel gasket and a spring are added, and the battery is sealed with a button battery sealing machine to complete the assembly of the LiFePO4||CSE||Li full battery.

[0072] Lithium iron phosphate was selected as the positive electrode material, and the cycling performance of the LiFePO4||CSE||Li full battery at 1C rate was tested. Figure 6 It shows that the LiFePO4||CSE||Li full battery based on the BST-PVH quasi-solid electrolyte prepared in Example 1 has a high discharge capacity of 136 mAh / g at a rate of 1C. After 170 cycles, the discharge capacity remained at 119 mAh / g, the capacity retention rate exceeded 87%, and the charge and discharge efficiency was close to 100%. These results show that the BST-PVH quasi-solid electrolyte exhibits excellent cycle stability and can effectively improve the performance and life of the battery.

[0073] Comparative Example 1: The preparation method of PVH solid electrolyte is specifically completed according to the following steps:

[0074] 0.3 g PVDF-HFP and 0.2 g LiFSI were dissolved in 3 mL N,N-dimethylformamide and magnetically stirred at 25 °C for 12 h to obtain a backfill solution; 300 μL of the backfill solution was dripped onto a glass plate and then placed in an oven at 55 °C for 24 h to obtain a solid electrolyte (PVH quasi-solid electrolyte), which was transferred to an argon-filled glove box for later use. Ionic conductivity and lithium ion transfer number (t Li + ); The test results show that the ionic conductivity of PVH quasi-solid electrolyte is 4.3×10 -4 S / cm,t Li + =0.16. The electrochemical stability window of the PVH quasi-solid electrolyte is 4.48 V. The limiting current density of the PVH quasi-solid electrolyte was tested by assembling a lithium symmetric battery and was 0.75 mA / cm 2 At the same time, at 0.1mA / cm 2 The current density and 0.1 mAh / cm 2 The battery life test was carried out at a surface capacity of more than 500 hours.

Claims

1. A method for preparing a high dielectric constant fiber-reinforced solid electrolyte, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of barium strontium titanate nanofibers: ①, dissolving polyvinyl pyrrolidone in anhydrous ethanol to obtain solution A; ②, dissolving barium acetate and strontium acetate in a mixed solution of glacial acetic acid and deionized water to obtain solution B; ③. Under magnetic stirring conditions, mix solution A and solution B evenly, then add tetrabutyl titanate and stir evenly to obtain a precursor solution for electrospinning; ④, degassing the precursor solution of electrospinning under vacuum conditions for a period of time, then loading it into a syringe, and fixing it on an electrospinning device for electrospinning. After the electrospinning is completed, the obtained fiber film is placed in the air, heated to 800°C to 1100°C, and calcined for a period of time in an air atmosphere at a temperature of 800°C to 1100°C to obtain a barium strontium titanate nanofiber film; 2. Preparation of fiber-reinforced solid electrolytes: PVDF-HFP and LiFSI were dissolved in N,N-dimethylformamide and magnetically stirred at room temperature for a period of time to obtain a backfill solution; the backfill solution was dripped onto the surface of the barium strontium titanate nanofiber film, and then placed in an oven to dry for a period of time to obtain a high dielectric constant fiber-reinforced solid electrolyte, which was transferred to a glove box filled with argon for use.

2. The method for preparing a high dielectric constant fiber reinforced solid electrolyte according to claim 1, characterized in that The mass ratio of the polyvinyl pyrrolidone described in step 1① to the volume ratio of anhydrous ethanol is (0.5g~0.7g):(6.5mL~9mL).

3. The method for preparing a high dielectric constant fiber reinforced solid electrolyte according to claim 1, characterized in that The volume ratio of glacial acetic acid to deionized water in the mixed solution of glacial acetic acid and deionized water described in step 1② is (3-5):(1-1).

4. The method for preparing a high dielectric constant fiber reinforced solid electrolyte according to claim 1, characterized in that The mass ratio of barium acetate described in step 1② to the volume ratio of a mixed solution of glacial acetic acid and deionized water is (2g~3g):(9mL~14mL); the mass ratio of strontium acetate described in step 1② to the volume ratio of a mixed solution of glacial acetic acid and deionized water is (0.4g~0.5g):(3.5mL~4.2mL).

5. The method for preparing a high dielectric constant fiber reinforced solid electrolyte according to claim 1, characterized in that The volume ratio of solution A and solution B described in step 1③ is (7-8):(6-7); the volume ratio of tetrabutyl titanate described in step 1③ to the total volume ratio of solution A and solution B is (1-2):(4-9).

6. The method for preparing a high dielectric constant fiber reinforced solid electrolyte according to claim 1, characterized in that The heating rate described in step 1④ is 5℃ / min~10℃ / min; the calcination time described in step 1④ is 4h~6h.

7. The method for preparing a high dielectric constant fiber reinforced solid electrolyte according to claim 1, characterized in that The process parameters of the electrospinning described in step 1④ are: using a No. 20 needle, setting the liquid supply rate to 1mL / h~2mL / h, the voltage to 18kV~25kV, and the distance between the needle and the receiving electrode to 15cm~18cm.

8. The method for preparing a high dielectric constant fiber reinforced solid electrolyte according to claim 1, characterized in that The degassing time described in step 1④ is 5min to 10min; the thickness of the barium strontium titanate nanofiber film described in step 1④ is 120μm to 150μm.

9. The method for preparing a high dielectric constant fiber reinforced solid electrolyte according to claim 1, characterized in that The mass ratio of PVDF-HFP described in step 2 to the volume ratio of N,N-dimethylformamide is (0.3g-0.5g):3mL; the mass ratio of LiFSI described in step 2 to the volume ratio of N,N-dimethylformamide is (0.2g-0.3g):3mL.

10. The method for preparing a high dielectric constant fiber reinforced solid electrolyte according to claim 1, characterized in that The ratio of the volume of the backfill solution in step 2 to the surface area of ​​the barium strontium titanate nanofiber film is 300 μL: (2 cm 2 ~3cm 2 ); the magnetic stirring time at room temperature in step 2 is 10h to 12h; the drying temperature in step 2 is 50°C to 55°C, and the drying time is 24h to 48h.

Citation Information

Patent Citations

  • Preparation method of multifunctional gel polymer electrolyte with gradient barium titanate content

    CN108808077A

  • Electrolyte

    CN109417189A

  • All-solid polymer electrolyte and rechargeable chloride ion battery

    CN109546209A

  • Preparation method and application of titanium nitride fiber reinforced quasi-solid electrolyte

    CN116742111A

  • Preparation method of bead-like barium strontium titanate nanofiber with giant dielectric low loss

    CN118996677A